Different strategies for the diagnosis of ovine brucellosis by Brucella ovis in an endemic flock from argentina - Fiorentino, M.A. (2017)
Brucella ovis is the etiological agent of contagious epididymitis in rams. Prevalence increases when biannual control was not performed in B. ovis endemic flocks. Diagnosis is based on clinical examination, serological tests and bacteriological isolation of B. ovis from semen. Semen analysis by PCR technique complements the direct diagnosis for the detection of B. ovis or other reproductive pathogens in sheep. In this work, different strategies for the diagnosis of contagious epididymitis in a flock, which this disease has been apparently controlled, were compared. Twenty-two rams were clinically examined and serum samples were analyzed by different serological tests. Semen samples were cultured in bacteriological media and were evaluated by multiplex PCR. Rams with a positive culture were necropsied and testes, epididymis, vesicular glands and ampullae were taken and studied by histopathology. B. ovis shedding in semen was significantly associated with the seropositivity and genital tract histopathological lesions. Multiplex PCR showed a similar sensitivity to semen culture and could be used as a complementary test for the direct diagnosis of B. ovis. Although this study involved a low number of animals, it provides useful information for the diagnosis of ovine brucellosis in an endemic flock and reinforces the need for biannual control.